2015
DOI: 10.1128/jvi.03390-14
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Codon Usage Impairs mRNA Accumulation: the Case of the v-FLIP Gene of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Like cellular FLIPs, the v-FLIP contains death effector domains (DEDs) (9), but unlike its host homologs, it does not appear to directly modulate caspase activation from the plasma membrane. Rather, it interacts with cytosolic IKK-␥ (10), leading to phosphorylation and proteasomal degradation of IB, the inhibitor of the transcription factor NF-B. As a result, NF-B undergoes constitutive activation, leading to the expression of a proinflammatory (11) and antiapoptotic (12) program. The antiapoptotic aspect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, vFLIP expression is reduced in infected cells due to inefficient codon usage. This low level expression is advantageous to the virus, as codon optimization resulted in inefficient lytic induction (Bellare et al, 2015). These observations suggest that vFLIP must maintain a delicate balance.…”
Section: Introductionmentioning
confidence: 99%
“…However, vFLIP expression is reduced in infected cells due to inefficient codon usage. This low level expression is advantageous to the virus, as codon optimization resulted in inefficient lytic induction (Bellare et al, 2015). These observations suggest that vFLIP must maintain a delicate balance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Vogt et al found a similar effect, reporting that ORF57 is required to sustain the levels of some viral mRNAs containing higher AT nucleotide content, which they propose is suboptimal compared to cellular nucleotide content [86]. In a separate study vFLIP was demonstrated to have suboptimal codon usage, which impaired vFLIP RNA accumulation [87]. In this case, the resulting low levels of vFLIP were optimal for lytic virus production [87].…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%
“…In a separate study vFLIP was demonstrated to have suboptimal codon usage, which impaired vFLIP RNA accumulation [87]. In this case, the resulting low levels of vFLIP were optimal for lytic virus production [87]. This suggests that codon and sequence composition may be used by KSHV to further modulate its gene expression.…”
Section: Post-transcriptional Control Of Viral Gene Expressionmentioning
confidence: 99%
“…Some of these genes show intrinsic features which likely minimize exposure to CD8+ T cells by restricting synthesis of their encoded protein, reducing the supply of defective ribosomal products (DRiPs) that are thought to be the source of CD8+ T cell peptide-epitopes[6]. Firstly vFLIP utilizes inefficient codons resulting in the production of unstable mRNA and low levels of protein expression[7]. Secondly LANA encodes extensive repeat sequences which restrict translation and proteasomal mediated destruction[8], minimizing epitope presentation from this protein to CD8+ T cells[9].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that knock down of vFLIP induced sensitivity to Fas ligation indicates that this viral protein can interfere with this apoptotic pathway[18], however vFLIP is thought to be expressed at low levels within infected cells[7]; whether other viral proteins contribute to this inhibition is unclear. An understanding of whether other latent proteins inhibit pathways induced by extrinsic apoptotic stimuli would allow the rational design of interventions to inhibit these functions and restore sensitivity to T cell effector mechanisms.…”
Section: Introductionmentioning
confidence: 99%